Comparison between models of global solar radiation in “Alto Pantanal” region, Mato Grosso do Sul State, Brazil - de Oliveira, Gabriel Queiroz; Biscaro, Guilherme Augusto; Lopes, Adriano da Silva; Jung, Leandro Henrique; Schwerz, Francielli (Comunicata Scientiae, 2014)
Solar radiation is a meteorological component of great importance to soil-plant-atmosphere processes, and the majority of weather stations do not register this component since they do not have the equipment for its quantification, having to rely on empirical models for estimation. The objective of this study was to evaluate the efficiency of four models to estimate solar radiation for the annual, rainy and dry periods in the Alto Pantanal region of Mato Grosso do Sul, Brazil. This study was conducted using meteorological data obtained between January 2008 and December 2011 from the automatic station located in Aquidauana, belonging to the network of meteorological stations of the National Institute of Meteorology (INMET). The data collected included maximum and minimum temperatures, and solar radiation. The Annandale, Bristow-Campbell, Hargreaves-Samani and Weiss empirical models were evaluated, and all were compared with the solar radiation value measured by the meteorological station. In the Alto Pantanal region of Mato Grosso do Sul, regardless of the time of year, the Bristow-Campbell model is recommended to estimate solar radiation.